Shadows of very high-frequency oscillations can be detected in lower frequency bands of routine stereoelectroencephalography - Vasickova, Zuzana; Klimes, Petr; Cimbalnik, Jan; Travnicek, Vojtech; Pail, Martin; Halamek, Josef; Jurak, Pavel; Brazdil, Milan (Scientific reports, 2023)
Very high-frequency oscillations (VHFOs, > 500 Hz) are more specific in localizing the epileptogenic zone (EZ) than high-frequency oscillations (HFOs, < 500 Hz). Unfortunately, VHFOs are not visible in standard clinical stereo-EEG (SEEG) recordings with sampling rates of 1 kHz or lower. Here we show that "shadows" of VHFOs can be found in frequencies below 500 Hz and can help us to identify SEEG channels with a higher probability of increased VHFO rates. Subsequent analysis of Logistic regression models on 141 SEEG channels from thirteen patients shows that VHFO "shadows" provide additional information to gold standard HFO analysis and can potentially help in precise EZ delineation in standard clinical recordings.
Keywords: stereotaktické techniky; Stereotaxic Techniques; elektroencefalografie; vysokofrekvenční ventilace; Electroencephalography; Blood Coagulation Tests; lidé; High-Frequency Ventilation; vyšetření krevní srážlivosti; Humans